A case-based review of urachal carcinoma with mixed small cell neuroendocrine and adenocarcinoma components, with one new case report and analysis of nine published cases - Chu, Junhao; Zhai, Jiwei; Ma, Qimei; Zhang, Zhihui; Yuan, Yanhua; Yuan, Huisheng; Wei, Chunxiao; Wang, Muwen (Frontiers in Endocrinology, 2025)
IntroductionUrachal carcinoma (UrC) is an uncommon malignant neoplasm arising from urachal remnants and represents only 0.01%–0.7% of bladder cancers. Adenocarcinoma—usually of the intestinal type—accounts for over 80% of cases, whereas neuroendocrine carcinoma (NEC) is exceedingly rare. Fewer than ten cases of urachal NEC have been documented in the English-language literature, most diagnosed at advanced stages with poor outcomes. We report an additional case and review published data to enhance clinical recognition and management of this ultra-rare tumor.Case presentationA 43-year-old woman presented to Shandong Provincial Hospital, Shandong First Medical University, after a urachal midline mass was incidentally detected on routine health examination. Preoperative tests showed a CEA level of 7.28 ng/mL. CTU revealed a 3.9 × 2.7 × 2.4 cm cystic–solid lesion at the anterior bladder wall, suspicious for urachal malignancy. Cystoscopic biopsy confirmed small-cell NEC. The patient underwent laparoscopic urachal resection with umbilicus preservation, extended partial cystectomy, and bilateral pelvic lymphadenectomy. Postoperative pathology showed a mixed urachal carcinoma composed of ~80% small-cell NEC and ~20% adenocarcinoma, forming a 4.5 × 3 × 1.5 cm cystic–solid mass. Margins and lymph nodes were negative. Immunohistochemical analysis showed a high Ki-67 labeling index (80%) and positive staining for synaptophysin (Syn), chromogranin A (CgA), insulinoma-associated protein 1 (INSM1), cytokeratin 20 (CK20), and mutant-pattern p53. Retinoblastoma protein (RB) and GATA-3 were negative. The patient received four cycles of adjuvant etoposide–cisplatin (EP) chemotherapy. Surveillance with tumor markers and whole-abdominal CT every three months showed no evidence of recurrence at the 8-month follow-up.ConclusionUrachal NEC with mixed small-cell and adenocarcinoma components is an exceptionally rare and highly aggressive malignancy lacking standardized diagnostic or therapeutic guidelines. Complete surgical excision with negative margins remains the mainstay of treatment, while adjuvant regimens are typically adapted from small-cell carcinoma protocols of the lung or urinary tract. We report a case managed with umbilicus-sparing urachectomy and extended partial cystectomy followed by EP chemotherapy, together with a review of nine previously published cases. These findings provide literature-based evidence to guide individualized management and inform future multidisciplinary research.